Understanding Community Involvement Behaviors in Waste Bank Programs: A Qualitative Study - Sri Hidayat; Bakhrani Rauf; Moh. Ahsan S Mandra (Pubmedia Social Sciences and Humanities, 2025)
This study aims to examine the factors shaping community involvement with the Waste Bank Program in Makassar City, focusing on sustaining pro-environmental behavior. These findings highlight that effective participation is shaped by the intersection of institutional frameworks and personal drivers rather than environmental awareness alone. The study contributes by integrating behavioral theories, social capital, and economic mechanisms into a single model. Insights offer actionable strategies for policymakers to strengthen capacity building, enhance transparency of incentive systems, and improve leadership credibility to sustain long-term community participation.